Factors Associated with Mortality in Patients with Autoimmune Diseases Admitted to the Intensive Care Unit in Bogota, Colombia - Carrizosa, Jorge Armando; Aponte, Jorge; Cartagena, Diego; Cervera, Ricard; Ospina, Maria Teresa; Sanchez, Alexander (Frontiers in Immunology, 2017)
Patients with autoimmune diseases (AD) are a challenge for the intensivist; it is hard to differentiate infection, disease activity, and combinations of both, leading to high mortality. This study is a retrospective analysis of 124 critically ill patients admitted to the Intensive Care Unit (ICU) in a University Hospital between 2008 and 2016. Bivariate case-control analysis was performed, using as case patients who died, later logistic regression model with variables that were associated with mortality was conducted. Four variables consistently associated with mortality in the logistic regression model, which had adequate prediction parameters found (Hosmer & Lemeshow = 0.760 R square Nagelkerke = 0.494). The risk of death was found statistically associated with: shock at admission to ICU (OR: 7.56; 95% CI 1.78 to 31.97, p = 0.006), hemoglobin level below 8 g / dL (OR: 16.12; 95% CI 3.35 to 77.52, p = 0.001), use of cytostatic prior to admission to the ICU (OR: 8.71; 95% CI 1.23 to 61.5, p = 0.03) and low complement C3 (OR: 5.23; 95% CI 1.28 to 21.35, p = 0.02). These variables could guide clinicians in early identification of patients with AD with increased risk of death during hospitalization, leading to initial therapies seeking to improve survival. These results should be evaluated prospectively in future studies to establish its predictive power.